Optimizations for FPGA-Based Ultrasound Multiple-Access Spread Spectrum Ranging. (4th June 2020) - Segers, Laurent; Braeken, An; Touhafi, Abdellah
Abstract : Indoor localization based on ultrasound signals has been carried out by several research groups. Most of the techniques rely on a single ultrasound pulse ranging, where the Time of Flight between the ultrasound emitters and a receiver is computed. Ultrasound orthogonal modulation techniques have also been investigated and allow to compute the range between the receiver and multiple simultaneous emitters with increased accuracy. However, no comparative investigation on the possibilities of each of the modulation techniques, comprising Direct Sequence Spread Spectrum, Frequency Hopping Spread Spectrum, and Chirp Spread Spectrum, could be found. Also, common optimized demodulation and correlation techniques for FPGA ready implementations are not widely available. Moreover, the hardware requirements for capturing modulated ultrasound signals could not be found for all the techniques. In this work, the different modulation techniques are optimized and implemented on an FPGA. A dedicated custom ultrasound MEMS-based receiver hardware for broadband ultrasound signal capturing is developed. Several modulation parameters are developed and applied for optimized signal processing. The FPGA resource consumptions are evaluated for the implemented methods. All methods are compared against the regular pulse ranging method, in both single-access and multiple-access ranging mode. Results show that, on average, up to 8 ultrasound-modulated emitters with an orthogonal sequence of length 63 can be demodulated on a Zynq7020 FPGA. In most cases, ranging up to 8 m is demonstrated in both single- and multiple-access mode, with accuracies generally remaining at a centimeter level. The requirements and capabilities for each of the modulation schemes are highlighted in the conclusions.